2019
DOI: 10.4103/jpbs.jpbs_117_18
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-mediated cytotoxic effect of Caralluma adscendens var. attenuata on colon (HT29) and Hepatic (HepG2) cancer cell lines

Abstract: Introduction: Caralluma adscendens var. attenuata (Wight) Grav. and Mayur., a member of Apocynaceae, is a perennial stem succulent plant with wide distribution in tropics and subtropics of the world. This plant is reported for the presence of steroids, flavonoids, saponins, triterpenes, and pregnane glycosides, and is known to have antidiabetic and antiulcerogenic properties. Materials and Methods: In this study, an attempt was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…has shown that most of these plant species could be possible sources of new active compounds. In addition to other metabolites such as flavonoid glycosides, pregnane glycosides were reported to be the most characteristic constituents of this genus. Several recent studies highlight their importance as medicinal plants to fight against particular diabetes, obesity, gastrointestinal problems, and cancer. For instance, the raw fresh young pieces of Caralluma hexagona (Syn; Monolluma hexagona, Caralluma shadhbana) are eaten as a cure for diabetes, abdominal pain, and stomach ulcers in traditional medicines in Yemen and Saudi Arabia. , …”
Section: Introductionmentioning
confidence: 99%
“…has shown that most of these plant species could be possible sources of new active compounds. In addition to other metabolites such as flavonoid glycosides, pregnane glycosides were reported to be the most characteristic constituents of this genus. Several recent studies highlight their importance as medicinal plants to fight against particular diabetes, obesity, gastrointestinal problems, and cancer. For instance, the raw fresh young pieces of Caralluma hexagona (Syn; Monolluma hexagona, Caralluma shadhbana) are eaten as a cure for diabetes, abdominal pain, and stomach ulcers in traditional medicines in Yemen and Saudi Arabia. , …”
Section: Introductionmentioning
confidence: 99%